Commentary on the Historia Apollonii Regis Tyri - Kortekaas, G. A. A. (Mnemosyne, bibliotheca classica Batava. Supplementum ;, 2007)
The story of Apollonius King of Tyre has rightly been called the most popular romance of the Middle Ages. From Iceland to Greece, from Spain to Russia, versions of this novel are recorded. It is the variation among the Latin versions and the numerous vernacular adaptations that make this story especially interesting. Shakespeare used and adapted it in his Pericles, Prince of Tyre. Its plot continues to fascinate us. Incest, deception, pirates, famine, sex and shipwreck form its tasty ingredients. Its links with the Greek novel, which today stands in the centre of scholarly interest, are striking. In this commentary the author even attempts to show that the novel originated in Greece, or more precisely Asia Minor, possibly inTarsus. The two recensions (RA and RB) are compared line by line, generally given preference to RA. All these aspects make the present book attractive to scholars of many different disciplines.